Penatalaksanaan Fisioterapi Pada Kondisi Frozen Shoulder Sinistra E.C Capsulitis Adhesiva Di Rsud Panembahan Senopati Bantul - Wijaya, Amwa Wigati; , Agus Widodo, S.Fis, M. Fis (2015)
Background: Frozen shoulder is pain resulting limited range of motion (LGS) on the shoulder. May arise because of the trauma, may also arise gradually without signs or history of trauma. This situation typically arises like symptoms can not combing because of pain around the front side of the shoulder. The pain is also felt when the arm was appointed to take something from his shirt pocket, this means active movement limited by pain. One of modalities to improve the range of motion is using the modality Short Wave Diathermy and training provision. Methods: This paper uses the case study method to management therapy 6 times. Results: After treatment for 6 times the obtained results of the assessment of pain in the left shoulder pain silent T1: 0 become T6: 0, pain motion T1: 8.6 into a T6: 7.1, tenderness T1: 7.2 into a T6: 5.4 , increase range of motion left shoulder sagittal plane T1: s (30-0-115) into T6: s (45-0-145), frontal plane T1: F (140-0-45) into T6: F (165- 0-59) transverse plane T1: T (F90) (48-0-60) into T6: T (F90) (60-0-74), increased functional activity scores ability T1: 93.75 becomes T6: 52.5. Conclusion: From the research that has been done, as evidenced by the use of SWD and exercise therapy modality for therapy obtained 6 times increase in impairment, functional limitation and disability.